The Governance of Urban Wastewater Treatment Infrastructure in the Greater Sekhukhune District Municipality and the Application of Analytic Eclecticism - Meissner, Richard (International Journal of Water Governance, 2015)
The governance of urban wastewater treatment works goes beyond the daily maintenance and upkeep of such systems. The governance includes interested and affected parties (stakeholders) further afield than the immediate proximity of the plant. As the concept might imply, governance would be an activity that is the purview of government only. This is not the case. Individuals and communities living downstream from such infrastructure and scientists can also become part of governance, either voluntarily or by default. Because of the wide range of stakeholders involved in the governance of wastewater infrastructure, we need to understand how and to what extent they influence governance. More so, it will be important to look also into the consequences of their actions while directly or indirectly governing wastewater infrastructure. In order to move beyond the traditional conceptualisation of governance as a government activity, this paper will utilise the ethos of analytic eclecticism and in particular six theories to investigate and widen our understanding of urban wastewater treatment governance. The six theories are (1) everyday international political economy, (2) interactive governance, (3) liberal pluralism, (4) interest group corporatism, (5) interest group pluralism and (6) psychological constructivism. This will, I hope, assist practitioners in formulating better policies as well as implementing them. The case study area is urban wastewater treatment in the Greater Sekhukhune District Municipality located in South Africa’s Limpopo Province. The Municipality faces a number of governance challenges like skills scarcity, a large geographic area to provide services to, rapid socio-economic development because of the mushrooming of platinum mines and a diversity of communities and other actors to providing services. The six theories all indicate different facets the actors employ or are affected by during the governing process. By employing the six theories, it becomes apparent that linear cause and effect relationships between the actors and the issue are impossible. It also shows that predicting the outcome of certain aspects, like the role of individuals, is impossible. It does paint, however, a fuller picture of what is happening in reality.